In order to simplify the expression 4(3x + y) + 2(x - 5y) + x² we just have to get rid of the parenthesis by distributing the products and then combine like terms, like this:
1. Get rid of the parenthesis
4(3x + y) + 2(x - 5y) + x² = 4×3x + 4×y + 2×x - 2×5y + x²
4×3x + 4×y + 2×x - 2×5y + x² = 12x + 4y + 2x - 10y + x²
2. Combine like terms
12x + 4y + 2x - 10y + x² = 14x - 6y + x² = x² + 14x - 6y
By simplifying the expression 4(3x + y) + 2(x - 5y) + x², we get x² + 14x - 6y, then the first option is the correct answer.